Transcripts Encoding the Androgen Receptor and IGF-Related Molecules Are Differently Expressed in Human Granulosa Cells From Primordial and Primary Follicles - Steffensen, Line L.; Ernst, Emil H.; Amoushahi, Mahboobeh; Ernst, Erik; Lykke-Hartmann, Karin (Frontiers in Cell and Developmental Biology, 2018)
Bidirectional cross talk between granulosa cells and oocytes is known to be important in all stages of mammalian follicular development. Insulin-like growth factor (IGF) signaling is a prominent candidate to be involved in the activation of primordial follicles, and may be be connected to androgen-signaling. In this study, we interrogated transcriptome dynamics in granulosa cells isolated from human primordial and primary follicles to reveal information of growth factors and androgens involved in the physiology of ovarian follicular activation. Towards this, a transcriptome comparison study on primordial follicles (n = 539 follicles) and primary follicles (n = 261) follicles) donated by three women having ovarian tissue cryopreserved before chemotherapy was performed. The granulosa cell contribution in whole follicle isolates was extracted in silico. Modelling of complex biological systems was performed using IPA® software. We found the granulosa cell compartment of the human primordial and primary follicles to be extensively enriched in genes encoding insulin-like growth factors (IGF)-related factors, and the Androgen Receptor (AR) enriched in granulosa cells of primordial follicles. Our study hints the possibility that primordial follicles may indeed be androgen responsive, and that the action of androgens represents a connection to the expression of key players in the IGF-signaling pathway including IGF1R, IGF2 and IGFBP3, and that this interaction could be important for early follicular activation. In line with this, several androgen-responsive genes were noted to be expressed in both oocytes and granulosa cells from human primordial and primary follicle. We present a detailed description of AR and IGF gene activities in the human granulosa cell compartment of primordial and primary follicles, suggesting that these cells may be or prepare to be responsive towards androgens and IGFs